"STAGES OF FORMATION AND DEVELOPMENT OF MEDIAMADANIATIN" - Erkabayeva Nigora Shermatovna, Yakubjonova Maftunakhan Islamjon Kizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article considers the approach of cultural studies as a key factor in the organization of modern higher education, describes the content of the concept of media culture and its stages of formation and development.